Chitogel with deferiprone following endoscopic sinus surgery: improved wound healing and microbiome - Megow, Anna; Bouras, George; Alsuliman, Yazeed; Cooksley, Clare; Vyskocil, Erich; Murphy, William; Vreugde, Sarah; Wormald, Peter-John (Frontiers in Surgery, 2024)
Background Adhesion formation, sinus ostial narrowing, and presence of pathogenic bacteria are associated with poor outcomes following endoscopic sinus surgery (ESS) for chronic rhinosinusitis. Chitogel has been shown to improve wound healing, restore a healthier microbiome, and reduce post-operative infections post ESS. Deferiprone has antibacterial properties and has been shown to reduce adhesion formation. The aim of the study was to assess whether the addition of low concentration deferiprone to Chitogel further improves surgical outcomes following ESS compared with Chitogel alone. Methods In this double-blinded trial, 45 patients undergoing ESS were prospectively recruited. At the end of the surgery, patients were randomised to receive Chitogel alone, Chitogel with 1 mM of deferiprone, or Chitogel with 5 mM of deferiprone to one side of the sinuses (allowing the other side to serve as control). Patients underwent routine follow-ups with symptom questionnaires and nasoendoscopies performed at 2, 6, and 12 weeks post-operatively. Sinus ostial measurements, microbiology, and microbiome swabs from bilateral middle meatuses were collected intraoperatively and at 12 weeks post-operatively. Results A significant improvement in the endoscopic appearance of the sinuses and frontal ostial patency was noted at 12 weeks post-operatively (p < 0.05) in all three treatment groups compared with the control. There was no significant difference noted between patients who received Chitogel alone and those who received Chitogel with 1 or 5 mM deferiprone. Conclusion Chitogel alone, Chitogel with 1 mM deferiprone, and Chitogel with 5 mM deferiprone used following ESS led to a significant improvement in endoscopic appearance of the sinuses and frontal ostial preservation at 12 weeks post-operatively. No significant difference was found with the addition of deferiprone to Chitogel.